Finding Optimal LSB Substitution Using Ant Colony Optimization Algorithm - Ching-Sheng Hsu; Shu-Fen Tu (2010 Second International Conference on Communication Software and Networks, 2010)
The Least Significant Bit (LSB) Substitution is a kind of information hiding method. The secret message is embedded into the last r bits of a cover image to get away from the notice of hackers. The security and stego-image quality are two main issues of the LSB substitution method. Therefore, some researchers propose an LSB substitution matrix to address these two issues. Finding an optimal LSB substitution matrix can be seen as a problem of combinatorial optimization. There are 2 r ! feasible solutions, hence the search space grows notably when r increases. Consequently, an efficient method to construct the matrix is necessary. In this paper, we apply the Ant Colony Optimization Algorithm to construct an optimal LSB substitution matrix. The experimental results show that ACO can find optimal LSB substitution matrix efficiently and improve the qualities of the stego-images.